GAMBARAN MOTIVASI BELAJAR PESERTA DIDIK PADA PEMBELAJARAN DARING SELAMA PANDEMI COVID 19 - Mohamad Hendri Pranjani; Asep Samsudin; Muhamad Rezza Septian (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
in conventional learning activities during the COVID-19 pandemic. This study aims to describe the learning motivation of students at SMP Bhakti Mulya Batujajar during the covid-19 pandemic. This study uses a descriptive quantitative approach. The sample of this study involved 100 students at SMP Bhakti Mulya Batujajar. The data collection technique in this study used a learning motivation questionnaire with a total of 25 statement items and made a google form to be easily accessed by students. Data analysis using guttmen scale. The results showed that the majority of students' learning motivation was in the low category, which amounted to 48 students (48%) have low learning motivation such as less active in the learning process and lack of enthusiasm for learning, for the medium category 23 students (23%) and the high category amounted to 29 students (29%) had high motivation.  Keywords: : Online Learning, Learning Motivation, Covid-19 Pandemic